The Safety of Haemophilus influenzae Type b/Polyribosylribitol phosphate-Tetanus (Hib/PRP-T) Vaccine, Phase I Study - Kusnandi Rusmil; Eddy Fadlyana; Rachmat Gunadi; Novilia Sjafri Bachtiar; Hadyana Hadyana (Faculty of Medicine Universitas Padjadjaran, 2015)
Objective: To assess the safety and immunogenicity of Haemophilus influenzae type b/polyribosylribitol phosphate-Tetanus (Hib/PRP-T) liquid vaccine in healthy adults.Methods: An open label prospective intervention phase I study was conducted in Dr. Hasan Sadikin General Hospital from November to December 2010. Healthy adults aged 18−40 were eligible to participate. Participants received one dose of Hib/PRP-T liquid vaccine. Blood samples were taken before, 4 days and 1 month after vaccination. For a 28-day period following vaccination, solicited adverse events were collected in the subjects’ diary and assessed afterward. Results: Neither local reactions nor immediate systemic events were observed during a 30-minute period after immunization. There were no serious local or systemic reactions in this study. All of local and systemic reactions observed were slight, transient, self-limiting in time, without lasting for more than 72 hrs. after the administration of the vaccine, and resolved without any medical intervention. Hematologic and biochemical indices before and 4 days after vaccination showed in normal limits. All subjects (100%) reached protective levels of antibodies (seroprotectivity) against Hib. All subjects demonstrated antibodies performing high bactericidal activities 1 month after immunization. Conclusions: This study demonstrated that liquid Hib/PRP-T vaccine is highly immunogenic and have a beneficial safety when administered to healthy adults. Keywords: Adults, Hib vaccines, immunogenicity, safety DOI: 10.15850/ijihs.v3n2.584